Information Literacy and Theological Librarianship Theory and Praxis - Smiley, Bobby (2019)
For librarians working in research, reference, and instruction, information literacy (IL) is foundational to their work. Since the advent of the Association of College and Research Libraries' Framework for Information Literacy for Higher Education, IL has been substantially reimagined both theoretically and in professional practice. While much attention and scholarship has focused on broad-based, undergraduate education, there has been less work on information literacy for specific disciplines, such as theological and religious studies, or in library settings with unique curricular and professional needs. Information Literacy and Theological Librarianship: Theory & Praxis gathers together reflective practices and theoretical explorations from librarians across a range of theological libraries, including research universities with divinity schools, seminaries, religious universities, and small liberal arts colleges. This volume engages key concepts and concerns in information literacy pedagogy for theological libraries, and furnishes applied examples drawn from instructional experience. Placing the Framework in conversation with the study of religion and theological education, Information Literacy and Theological Librarianship provides theological and religious studies librarians working in different academic environments with concrete and practical ways to extend their own work on information literacy that is grounded in pedagogy and applicable to the unique features of theological librarianship.